Impressions on the Old Chain (1750-1808) - Lucheti, Nayara Vignol [UNESP] (Univ Federal Rio Grande Sul, Programa Pos-graduacao & Historia, 2017)
This article has as object the prison and the prisoners in the city of Sao Sebastiao do Rio de Janeiro during the colonial government, with emphasis on the period from 1750, when increases the city's importance in the Lusitanian Empire and ends a cycle of reforms in the jail, until 1808, date of the transfer of the court to Rio de Janeiro and moment when the prisons started to be built in separate of municipality. It will also be worked here the position of the government, care institutions and population in support of prisons and prisoners, and, still, how certain aspects of Rio de Janeiro's colonial society were related to the problems of mismanagement of justice and resources, which resulted in the precarious situation of public prisons in the city.
Keywords: Colonial Brazil; Rio de Janeiro; prisons